The antihyperglycaemic and antiobesity effects of selected compounds from garcinia malaccensis on 3t3-l1 adipocytes - Mohamed Amiroudine, Mohamed Zaffar Ali; Bakhtiar, Muhammad Taher (IIUM Press, International Islamic University Malaysia, 2017)
The increase incidence in diabetes-and obesity-related diseases in developed and developing countries has driven serious efforts towards the discovery of adipogenic differentiation-inhibitory compounds in natural products. Mangostins and triterpenoids from Garcinia have been reported to contain a wide range of bioactivities. However, its antidiabetic and antiobesity activity has not been previously addressed. With regard to the fact, this research is designed to study the antihperglycaemic and antiobesity effects of selected phytochemicals isolated from Garcinia malaccensis namely beta-mangostin and cycloartane triterpenoid. The compounds were tested for their antihyperglycaemic and antiobesity effects in 3T3-L1 adipocytes. In this study, we first elucidated the effects the compounds on the lipid accumulation of 3T3-L1 preadipocytes by using Oil Red O staining. The ability of the cell to uptake glucose was measured by liquid scintillation counter. Peroxisome proliferator-activated receptors gamma (PPARy), glucose transporter four (GLUT4) and leptin genes expression was determined by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). The results showed that β-mangostin reduced the triglyceride accumulation in 3T3-L1 adipocytes with highest lipid inhibition activity was observed at 50 μM concentration (p<0.05) when compared to MDI (0.5 mM 3-isobutyl-1-methyl-xanthine (IBMX), 0.25 mM dexamethasone, 1 μg/mL insulin) treated cells. On the other hand, treatment with cycloartane triterpenoid significantly induced lipid accumulation. Analyses of 2-deoxy-D-[3H] glucose uptake activities showed that all the compounds including the MDI, metformin and sodium orthovanadate (positive control) significantly (p<0.05) improved the glucose uptake when compared to the basal cell. In addition, evaluation by using the adipolysis kit (Cayman Chemicals) showed that β-mangostin increases the amount of free fatty acid (FFA) release. Further evaluation by the gene expression analysis showed that β-mangostin may reduce lipid accumulation by inhibition of the expression of PPARγ genes. In addition, induction of glucose uptake and free fatty acid release by β-mangostin was accompanied by increasing of mRNA expression of GLUT4 and leptin. Interestingly, mature 3T3-L1 cells treated with cycloartane triterpenoid was shown to enhance PPARγ and GLUT4 gene expression and decreased leptin expression. As a conclusion, these line of evidences indicated that β-mangostin and cycloartane triterpenoid derived from Garcinia malaccensis may become an interesting candidate for the prevention of metabolic disorders such as diabetes and obesity.